Metalliferous mineral exploration opportunities in Britain - T. B. Colman (The Institute of Materials, Minerals and Mining, 1991)
Paper presented at the MEP '89 conference held in Madrid, 13-15 November 1989. Britain has sustained an important metalliferous mining industry over many centuries. Recently, new geological concepts and exploration techniques have indicated that there is considerable potential for the discovery of a variety of deposit styles, often in previously neglected areas. The recent discoveries at Aberfeldy (Ba-Zn-Pb), Gairloch (Cu-Zn) and Cononish (Au-Ag)in Scotland and Curraghinalt (Au-Ag) and Lack (Au-Ag-Pb) in Northern Ireland are illustrations of this potential. Some of the prospective areas for future exploration are described and an indication is given of the legislative framework within which mineral exploration and development are carried out